Studi Teoretis Struktur Elektronik dan Sifat Transisi Spin Kompleks [Fe(dpa)2(NCS)2] - Yusthinus Thobias Male; Djulia Onggo; Muhamad Abdulkadir Martoprawiro; Ismunandar Ismunandar (Jurnal Matematika & Sains, 2009)
The computational method B3LYP*/6-31G(d) has been used for predicting the mononuclear spin transition (ST) complexes properties, i.e. [Fe(dpa)2(NCS)2] with cis and trans isomers. Computational results showed that in vacuum and methanol, cis-[Fe(dpa)2(NCS)2] isomer gave a reasonable value of âEel for ST. In methanol, the cis isomer was more stabilized because that isomer showing more higher dipole moments (21,59 D) than the trans isomer and unsubstituted complex, [Fe(dpa)3]2+ (5,70 and 0,03 D). This results showed that if those complexes were synthesized, in the ambient temperature they have high spin properties but only cis-[Fe(dpa)2(NCS)2] isomer has ST properties. Analysis of main atomic orbitals populations showed that the electronic ground bands and the next ground bands are assigned to ligand-to-ligand charge-transfer (LLCT) transitions because of the charge transfer from NCS-ligand to the main ligand. It can be concluded that computational method B3LYP*/6-31G(d) gives more predictive power to mononuclear ST complex.